A Matrix Characterization of Statistical Convergence of Double Sequences - Miller, Harry I.; Miller-Van Wieren, Leila (Sarajevo Journal of Mathematics, 2024)
Fridy and Miller have given a characterization of statistical convergence for bounded single sequences using a family of matrix summability methods. In this paper we prove the analogous result for double sequences. 2000 Mathematics Subject Classification. 40D25, 40G99, 28A12